The Application of a Domino Train Game-Based Learning System in Improving Middle School Students' Understanding of Algebraic Operations - Warsali, Warsali; Kurniawan, Asep; Tabroni, Imam; Dewi, Maftuhah; Karim, Abdul (ZERO: Jurnal Sains, Matematika dan Terapan, 2024)
This study examines the effectiveness of using domino train games in teaching algebraic operations and how it improves students' understanding. The research employed Classroom Action Research (CAR) with both experimental and control groups. The experimental group was taught using the domino train game method, while the control group followed traditional teaching methods. The study was conducted at SMP Uswatun Hasanah during the 2019-2020 academic year, involving 64 seventh-grade students divided into two classes: class VII A (32 students) as the experimental group and class VII B (32 students) as the control group. Data were collected using pre-tests and post-tests to assess students' understanding of algebra, along with questionnaires to measure student engagement. The tests consisted of 10 essay questions on algebra. Validated closed-ended questionnaires were used to gather data on students' involvement in the learning process. Data analysis included normality tests, Mann-Whitney tests, and N-Gain calculations. Results showed that the experimental group experienced significant improvement, with an N-Gain of 0.493, while the control group had an N-Gain of -0.322. The findings indicate that the domino train game method is effective in enhancing students' understanding and participation in mathematics learning, providing an innovative alternative in teaching algebra.